Emergency Department Testing Patterns for Sexually Transmitted Diseases in North Texas. Issue 7 (July 2019) - Barnes, Arti; Jetelina, Katelyn K.; Betts, Andrea C.; Mendoza, Theresa; Sreeramoju, Pranavi; Tiro, Jasmin A.
Abstract : Background: Little is known about population-level sexually transmitted disease (STD) testing in emergency departments (EDs). We sought to explore STD testing patterns in EDs in a large, urban metroplex in North Texas, a high prevalence region. Methods: Emergency department claims data were extracted from the Dallas Fort Worth Hospital Council databank for patients attending 54 EDs in 4 counties (Dallas, Tarrant, Collin, and Denton) who were tested for an STD during an ED visit between July 2014 and June 2015. We analyzed patterns of testing for 3 types of STD tests: (1) combined gonorrhea and chlamydia DNA-based tests, (2) human immunodeficiency virus (HIV) antibody tests, and (3) syphilis serological tests. Results: Emergency departments administered at least 1 STD test to 65, 702 unique patients over 1 year; most were ethnoracial minorities (73%), female (72%), and had no known insurance (59%). Only 8% of patients received more than 1 of these tests at that same visit; of those, 90% were cotested for HIV. The most common diagnosis code associated with STD testing was "genital/urinary symptoms" (31%). The majority of tests took place at the ED of a single county-funded hospital (42%). Only 36% of all patients had visits that were deemed true emergencies. Conclusions: Most patients tested for syphilis, HIV, or chlamydia/gonorrhea in EDs received only 1 test type at that visit, and most visits were nonemergent in nature. Given shared risk factors for multiple STD and high coinfection rates, EDs serving high-risk populations could consider STD cotesting to help reduce transmission of undiagnosed, untreated infections. Abstract : A study of emergency departments in North Texas found most patients tested for sexually transmitted diseases were ethnoracial minorities with no known insurance presenting with nonemergencies. Few were tested for multiple sexually transmitted diseases.